Photography and the ‘Jeu des clefs’: À la recherche du temps perdu in the light of Paul Nadar's portraits - Yacavone, Kathrin (Edinburgh University Press, 2012)
The year 1978 saw the first exhibition of photographic portraits of Marcel Proust's family, friends and acquaintances taken by Paul Nadar, an event leading to renewed interest in the subject of À la recherche du temps perdu as a roman à clef. This article examines two interpretations of Proust's novel in the light of these images, as put forward by William Howard Adams and Roland Barthes. While Adams and Barthes both take George Painter's Proust biography as a starting point for their own readings of the photographs as ‘keys’ to the novel, they offer two contrasting perspectives on À la recherche: Adams emphasizes the transparent and positivistic connection between the author's life and work, whereas Barthes focuses on a more fluid, dialectical and productively ambiguous relation between the two. Both of these perspectives, but particularly Barthes's, it is argued, shed light on the novel's production and the broader, multi-faceted relations between photography, (auto)biography and literature.